Stability analysis of an SVIR epidemic model with non-linear saturated incidence rate - Khan, M.A. (Hikari Ltd., 2015)
In this paper, we present an SVIR epidemic model with non-linear saturated incidence rate. Initially the basic formulation of the model is presented. Two equilibrium point exists for the system; disease free and endemic equilibrium. The stability of the disease free and endemic equilibrium exists when the basic reproduction less or greater than unity, respectively. If the value of R0, less then one then the disease free equilibrium is locally as well as globally asymptotically stable, and if its exceeds, the endemic equilibrium is stable both locally and globally. The numerical results are presented for illustration. Â© 2014 Muhammad Altaf Khan et al.